Secondary Metabolites Production of Bacillus spp. Isolated from Sea Cucumbers (Holothuria scabra) and their Activity against Mycobacterium smegmatis - Maya Dian Rakhmawatie; Aida Zakiyatul Fikriyah; Ika Dyah Kurniati; Nanik Marfu'ati; Stalis Norma Ethica (Sanata Dharma University, 2023)
New anti-tuberculosis agents are very important due to Multidrug-Resistant and Extensively Drug-Resistant Tuberculosis problems. Mycobacterium smegmatis can be used to replace Mycobacterium tuberculosis as bacteria test to increase the velocity of anti-tuberculosis screening. To answer the need for new drugs, exploration of secondary metabolites from Bacillus spp. can be conducted. Bacillus spp. are known to produce antimicrobials, including discovery of iturins, fengycins, and pumilacidins. This study explored the Bacillus spp. isolated from fermented intestines of Holothuria scabra. The production of Bacillus sp. Holothuria scabra Fermented Intestine (HSFI) secondary metabolites was done using culture media containing starch as a carbon source, as well as yeast and peptone as a nitrogen source. Production capacity of secondary metabolites of Bacillus sp. HSFI was calculated, to determine its potential as an antibacterial producer. Inhibition testing of secondary metabolites of Bacillus sp. HSFI against M. smegmatis was performed using the Kirby-Bauer disk diffusion method. Based on the results of the inhibition test, it was concluded that Bacillus sp. HSFI-9 has the greatest potential to inhibit the growth of M. smegmatis, with a moderate inhibition (7.67 mm). Production of secondary metabolites from Bacillus sp. HSFI-9 is exceptionally good with an extract production capacity of 24.6 mg/L.